PENGETAHUAN ORANG TUA TERHADAP PERTUMBUHAN DAN PERKEMBANGAN BALITA MELALUI PENGGUNAAN BUKU KESEHATAN IBU DAN ANAK ( KIA ) - Gita Ayu Indria (Jurnal Inovasi Daerah, 2022)
Toddler Period is an important stage in the growth and development of toddlers which is often called the golden age. In that period there are changes in physical growth and changes in cognitive development which are fundamental to the later stages of growth and development. This study aims to find out that parents' knowledge about the stages of growth and development can affect the growth and development process of toddlers in Kuripan Kidul Village, Kesugihan District, Cilacap Regency. This research is in the form of analytical research with a Cross Sectional Study. The sample used parents of toddlers, they are 40 respondents obtained by cluster random sampling. The results of this study show that there are differences in parents with sufficient knowledge of growth and development of toddlers, so the growth and development of toddlers will be in accordance with the stages of growth and development that are in the mother and child health Book. The results of the chi-square statistical test obtained 12,477 with a p-value of 0.001 and 100 persen ownership of the mother and child health Book. In parents who have knowledge of the growth and development of toddlers, there are no deviations in the growth and development of toddlers.